Van Gogh: from painting to photography and to music Van Gogh: da pintura à fotografia e à música - Cássia Maria Popolin (Discursos Fotográficos, 2007)
Van Gogh portrays cuts of the act of planting, reaping, harvesting and bundling wheat. This article is aimed at doing a comparative update between the painter works and cane cutters portrayed by Gabriel Oliveira in Flórida Paulista (SP). By uniting both readings, it intends to construct a visual narrative of the song Cio da Terra, of Milton Nascimento and Chico Buarque. The goal is to search in the canvases and in the pictures, the visibility of the poem, and in the poem, the readability of the pictures, in order to create a sensation of “reader navigator” where he could sometimes navigate in the waters of image and then in the waters of text, constructing an deconstructing text and image poetically. Van Gogh retrata recortes do ato de plantar, ceifar, colher e enfeixar o trigo. Este artigo se propõe a fazer uma atualização comparativa de sua obra com as fotografias de cortadores de canade- açúcar, tomadas por Gabriel Oliveira em Flórida Paulista (SP). E, a partir da união dessas duas leituras, construir uma narrativa visual da música Cio da Terra, de Milton Nascimento e Chico Buarque. A proposta é buscar nas telas e nas fotografias a visibilidade do poema e, no poema, a legibilidade dos retratos para, com isso, propiciar uma sensação de “leitor navegador”, na qual ele possa ora navegar pelas águas da imagem, ora pelas águas do texto, construindo e desconstruindo poeticamente texto e imagem.